Self-Immolative nanoparticles for stimuli-triggered activation, covalent trapping and accumulation of in situ generated small molecule theranostic fragments - Zexuan Ding; Jie Cen; Yun Wu; Kai Zhong; Guhuan Liu; Jinming Hu; Shiyong Liu (Giant, 2020)
Small molecule theranostic agents suffer from fast blood clearance whereas nanoparticle ones are incapable of molecular functions and often nondegradable. We propose to bridge the gap between nanoparticles and small molecule agents based on self-immolative polymers which undergo triggered cascade depolymerization at the chain level. Amphiphilic block copolymers containing side chain-functionalized depolymerizable block self-assemble into micellar nanoparticles. Upon triggering with reactive oxygen species (ROS) and acidic pH, nanoparticles self-immolate into electron-deficient small molecule azaquinone methide (AQM) derivatives, which are capable of efficient addition reactions with biologically relevant nucleophiles. By taking advantage of this feature, we achieve stimuli-activatable 19F NMR/MR imaging and 19F/1H dual-modality MR imaging. Upon cellular uptake, AQMs generated during depolymerization react with intracellular thiol-relevant substrates including GSH and thiol-containing proteins. Starting from self-immolative nanoparticles functionalized with DOTA-Gd, we demonstrate unprecedented long-term in vivo 1H MR imaging of tumor-bearing mice via the in situ covalent trapping strategy.